Non-Invasive Liver Fibrosis Scores Are Associated With Contrast-Associated Acute Kidney Injury in Patients Undergoing Elective Percutaneous Coronary Intervention. (April 2023) - He, Hao-Ming; He, Chen; You, Zhe-Bin; Zhang, Si-Cheng; Lin, Xue-Qin; Luo, Man-Qing; Lin, Mao-Qing; Zhang, Li-Wei; Lin, Kai-Yang; Guo, Yan-Song
Previous studies have demonstrated that non-invasive liver fibrosis scores (LFSs) are associated with kidney function deterioration. This study aimed to assess the predictive performance of LFSs in contrast-associated acute kidney injury (CA-AKI) in coronary artery disease (CAD) patients undergoing elective percutaneous coronary intervention (PCI). This retrospective study involved 5627 patients. The frequency of CA-AKI was 6.3% (n = 353). In a multivariate logistic analysis after adjustment, non-invasive LFSs, including fibrosis-5 score (FIB-5), fibrosis-4 score (FIB-4), aspartate aminotransferase to alanine aminotransferase ratio (AAR), and aspartate aminotransferase to platelet ratio index were independent risk factors for CA-AKI (all P < .05), whereas the Forns score was not ( P > .05). The highest predictive performance was observed for FIB-5 (area under the curve [AUC] = .644) compared to other LFSs. A restricted cubic spline analysis confirmed approximately linear relationships between LFSs and risks of CA-AKI. Furthermore, adding FIB-5 (AUC = .747; net reclassification improvement [NRI] = .441, P < .001; integrated discrimination improvement [IDI] = .008, P < .001) or AAR (AUC = .747; NRI = .419, P < .001; IDI = .006, P = .010) to an established clinical risk model could significantly improve the prediction of CA-AKI. The LFSs were significantly associated with CA-AKI, possibly serving as predictive tools for early identification of CAD patients undergoing elective PCI that are at high risk of CA-AKI.